(untitled) (TAMADDUN NURI JURNALI, 2025)
This article explores the role of interactive teaching methods, particularly the project-based method, in developing foreign language communicative competence among students majoring in information technology. The effectiveness of this method is demonstrated through a student-led independent project to create a university newspaper. The article highlights how project-based learning contributes to the development of speaking skills, communication abilities, and teamwork competence.